Seldom ask, never tell : labor and discourse in Appalachia - Puckett, Anita, 1949- (Oxford studies in anthropological linguistics, 2000)
Puckett takes a new look at the relationship between language, society, and economics, by examining how people talk about work in a rural Appalachian community. Through analysis of conversations in casual yet commercial contexts, she finds that the construction and maintenance of this discourse is essential to socio-economic relationships.